Transformasi Digital Pegadaian Syari’ah: Tinjauan Ulang terhadap Akad Rahn dan Ijarah dalam Layanan Gadai Online - Farhanah, Farida Afnan; Nurrohmah, Lia; Destari, Ridha Nuri; J, Jaenudin; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Digital transformation at Pegadaian Syariah is an important step in responding to technological developments and the public’s need for fast and efficient financial services. Through the Pegadaian Digital Service (PDS), pawn transactions can now be conducted online without compromising sharia principles. This study aims to examine how the Rahn and Ijarah contracts are implemented in online pawn services and to assess their compliance with the provisions of fiqh muamalah and legal regulations in Indonesia. The method used is a qualitative approach with a literature study, involving analysis of DSN-MUI fatwas, Islamic economics literature, and official documents from Pegadaian Syariah. The results of the study show that the implementation of the Rahn and Ijarah contracts in digital form fulfills sharia requirements because it is transparent, uses valid electronic signatures, and operates under the supervision of the Sharia Supervisory Board (DPS). This digital transformation not only increases the efficiency and security of services but also expands public access to sharia-compliant finance and supports the realization of maqashid sharia, namely public benefit and justice in modern economic transactions.